EBI2 - Sensor for dihydroxycholesterol gradients in neuroinflammation - Kurschus, Florian; Wanke, Florian (Biochimie, 2018)
Dihydroxycholesterols such as 7α,25-dihydroxysterols (7α,25-OHC) and 7α,27-OHC are generated from cholesterol by the enzymes CH25H, CYP7B1 and CYP27A1 in steady state but also in the context of inflammation. The G-protein coupled receptor (GPCR) Epstein-Barr virus-induced gene 2 (EBI2), also known as GPR183, senses these oxysterols and induces chemotactic migration of immune cells towards higher concentrations of these ligands. We recently showed that these ligands are upregulated in the CNS in experimental autoimmune encephalomyelitis (EAE), an animal model for multiple sclerosis and that EBI2 enhanced early infiltration of encephalitogenic T cells into the CNS. In this short-review we discuss the role of dihydroxysterol-sensing by immune cells in neuroinflammation.